Negative Compressibility in the Monoclinic Octahedron Model Constructed by Hinging Wine‐Rack Mechanism. Issue 2 (18th September 2020) - Ma, Meng; Zhou, Xiaoqin; Liu, Hao; Wang, Haocheng
Abstract : Enlightened by the concept of crystal system, many of the 3D models with negative compressibility that have been proposed so far are cellular models with periodic arrays, which can be called as orthogonal models or tetragonal models. Therefore, a more effective method to design 3D models with negative compressibility by changing the system type of the existing models can be developed. Herein, a monoclinic octahedron model based on the tetragonal octahedron model studied previously is proposed and its compressibility property is analyzed in detail through theoretical modeling. The specific conditions for the model to obtain negative compressibility are given in the discussion of on‐axis mechanical properties. The study about off‐axis compressibility shows that in addition to the geometric features, the measuring direction of compressibility and the arrangement of framework may also have a great influence on negative compressibility effect of the model. Abstract : Herein, a new monoclinic octahedron model (image b, d) based on the tetragonal model (image a, c) is proposed and the conditions to obtain negative compressibility are given. Furthermore, model 1 can be reconstructed to get model 2 (image e), and comparsion between model 1 and 2 shows that the arrangement of the framework also greatly affects the negative compressibility property.